Analisis Aspek-Aspek Literasi Sains Pada Buku Kurikulum 2013 Tema 1 Kelas IV SD - Hirma Meuthia; Jon efendi; Riska Ahmad (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
Science education has a strategic role in preparing quality human resources to face this era of globalization. Science literacy is a measure of the success of science learning in schools. This study aims to determine the level of scientific literacy in 2013 Curriculum Book Theme 1 Class IV SD which emphasizes the dimensions of scientific literacy, including: science as a body of knowledge, science as a way to investigate, science as a way of thinking and interacting with science, technology and society.This type of research is a quantitative descriptive study. The population in this study were all material in the 2013 Curriculum Student Book Theme 1 Class IV SD. The sample in this study were several pages in the analyzed book that were related to scientific literacy with the sampling technique using purposive sampling. The instrument used is the observation result. The data is filtered using a category sheet containing the indicators of scientific literacy which are then identified in each paragraph, the occurrence of these indicators is converted into a percentage for each category. The results showed that in general, the books analyzed showed more aspects of science as science as a way of investigating by 48.5%; science as a body of knowledge of 26.5; science as a way of thinking of 22.1%, and the interaction of science, technology and society by 2.9%. Overall, the student books used reflect the four categories of scientific literacy but there is no balance in the four categories and there are several sub-indicators of aspects that do not appear in the book.